Completion Rates, Adverse Effects, and Costs of a 3-Month and 9-Month Treatment Regimen for Latent Tuberculosis Infection in California Inmates, 2011-2014. (May 2019) - Wheeler, Charlotte; Mohle-Boetani, Janet
Objectives: In California, about 80% of tuberculosis disease is caused by untreated latent tuberculosis infection (LTBI), and the rate of LTBI is higher among incarcerated persons (16%) than among nonincarcerated persons (6%). We compared 2 regimens to treat LTBI in an adult prison population in California: 9 months of twice-weekly isoniazid (9H; previous standard of care) and 12 once-weekly doses of isoniazid and rifapentine (3HP; introduced in 2011). Methods: We evaluated the rates of completion and discontinuation caused by hepatotoxicity among randomly selected patients with LTBI prescribed the 9H regimen in 2011 and among patients with LTBI prescribed the 3HP regimen who entered California prisons during September 2013–March 2014. We compared the cost per fully treated patient for the 2 regimens. Results: Of 92 patients treated with the 9H regimen, the treatment completion rate was 42% and discontinuation due to hepatotoxicity was 14%. Of 122 patients who accepted the 3HP regimen, the completion rate was 90% and discontinuation due to hepatotoxicity was 2%. The cost per fully treated patient for the 9H regimen was $981 and for 3HP was $652. Conclusions: In an incarcerated population, the 3HP regimen had a higher completion rate, lower hepatotoxicity, and lower cost per fully treated patient than the 9H regimen. If coupled with a high treatment initiation rate, the high rate of LTBI treatment completion with 3HP may contribute to reducing tuberculosis morbidity in California.